Platinum(II) Schiff Base Complexes as Photocatalysts for Visible‐Light‐Induced Cross‐Dehydrogenative Coupling Reactions. Issue 10 (1st July 2015) - Shelar, Deepak Prakash; Li, Ting‐Ting; Chen, Yong; Fu, Wen‐Fu
Abstract Four phosphorescent platinum(II) Schiff base complexes are screened for application in visible‐light‐induced cross‐dehydrogenative coupling (CDC) reactions. Preliminary studies show that, among the four platinum(II) complexes, Pt3 is an efficient catalyst for CDC reactions with oxygen as an oxidant. Light irradiation (λ>420 nm) on a mixture of the PtII complex, tertiary amine, and a variety of nucleophiles (nitroalkanes, ketones, or indoles) under aerobic conditions gives α‐functionalized tertiary amines in good to excellent yields. The photoluminescence quenching experiment reveals that the CDC reaction is initiated by photoinduced electron transfer from N‐phenyltetrahydroisoquinoline to the PtII complex. Further, electron spin resonance (ESR) measurements clearly indicate the formation of superoxide radical anions (O2.−) rather than singlet oxygen (1O2) during the photocatalytic reaction.